THE DIGITAL ECONOMY AND THE DIGITIZATION OF – PAST, PRESENT, AND FUTURE. - Romanovna, Topunova Irina; Sharapovna, Koroleva Nonna; Nikolaevna, Rybina Marina; Yurievna, Iatsenko Oksana (International Journal of Psychosocial Rehabilitation, 2020)
Currently, the world economic and social development is characterized by a significant impact of the process of digitalization - a new trend of social development based on the digital representation of information. Given the size of the economic and social life of both the individual country and the individual, digitalization ultimately leads to more efficient economic activity and better quality of life.But, on the other hand, significant amounts of information received from outside, the frequent need for remote management and rapid decision-making in conditions of incomplete, and in some cases unreliable, information- these are only a few challenges of the new post-industrial, digital economy, which has both positive and negative sides. Also, the unstable external environment is forcing humanity to reconsider its place in the modern global economy.Thus, as part of the development of digitalization, there is a problem of neutralizing the negative consequences and risk groups. In modern conditions, this is possible only with certain measures, which include the implementation of information security rules, which is the basic element of the security system. In turn, information security involves not only the protection of information from unauthorized access, transformation, and destruction but also the protection of information resources from external and internal influences aimed at violating their stable performance. Thus, the use of information security systems will lay a solid foundation for the formation of a fundamentally new platform for the further global development of the economy and society.